Peran TV Sekolah SMAN 105 Jakarta Timur dalam Komunikasi Pembelajaran Jarak Jauh - Anggraeni, Diana; Ahmad, Rosmalia; Rawi, Muhammad Farhan (Jurnal Dinamika Ilmu Komunikasi, 2025)
Covid-19 is a respiratory virus that has spread worldwide, including to Indonesia, prompting the implementation of PPKM and online teaching and learning activities. The goal is to investigate the role of school TV in the communication process for distance learning at SMAN 105 East Jakarta. A postpotivism paradigm with a qualitative approach was employed. Data were gathered through structured interviews with five informants and observations. The Miles and Huberman model of analysis was used, which included coding, data reduction, and data display. Source triangulation was carried out with various informants. A qualitative approach and postpotivism paradigm were applied. Five informants were interviewed in a structured manner to collect data, along with observations. The analysis process adhered to the data reduction, data display, and coding steps of the Miles Huberman model. Sources were triangulated across different informants. According to Laswell's communication model, research findings show that School TV serves as a tool for distance learning, a platform for creating short films, a means of documenting activities, and facilitating information exchange Students' understanding of course materials, inventiveness, engagement, and technological proficiency are all enhanced.